Sub-Total Loss of Lower Lip - Kiran M. Patel (Indian Journal of Plastic Surgery)
The full-thickness loss of lower lip may be due to chemical, electrical burns, cancrum oris, accidental injuries, maxillofacial injuries, gunshot wounds, after surgical excision and rarely due to animal bite. An uncommon cause of the loss of the lower lip due to human bite and its subsequent repair by full thickness lip advancement and check rotation flaps would be presented through this paper.